AB0712 The influence of hand angulation on hand bone mineral density estimates using digital x-ray radiogrammetry. (23rd January 2014) - Pfeil, A.; Boettcher, J.; Froeber, R.; Sommerfeld, J.; Oelzner, P.; Wolf, G.
Abstract : Background: Digital X-ray radiogrammetry (DXR) is a computer-assisted technique to quantify cortical hand bone mineral density at the metacarpal bones in patients with rheumatoid arthritis. Objectives: The aim of this experimental study was to evaluate the influence of rotation of the metacarpal bones on measurements of bone mineral density (BMD) and the Metacarpal Index (MCI) using the DXR technique. Methods: Hand radiographs of a deceased male were performed at different angulations (between 0 to 19°). Bone mineral density and the Metacarpal Index of the hand were measured by DXR (Version 2, Sectra, Sweden) and the coefficients of variation were measured to verify the reliability and reproducibility of this radiogeometric technique. Results: Between 0 to 19° no significant changes of the coefficient of variation for bone mineral density and the Metacarpal Index were observed. Conclusions: The study revealed no significant influence of hand rotation on the measurements of metacarpal bone mineral density as estimated by DXR, indicating the capability of this technique to accurately quantify periarticular cortical bone mass. This is important especially in the field of rheumatoid arthritis as x-ray imaging involves intricate positioning of arthritic hands. Disclosure of Interest: None Declared